Modern military weapons - Cross, Robin (New York, NY : F. Watts, 1991)
Examines today's modern weapons of land, air, and sea; with special emphasis on the high tech "smart" bombs and missiles.
Includes index.
Wilson's Junior High School.
7.9
5-8
Keywords: Military weapons -- Juvenile literature; Weapons systems -- Juvenile literature; Military weapons; Weapons systems; Military weapons; Weapons